Indeks plak dan tingkat keparahan gingivitis anak tunagrahita (Intellectual Disability)Plaque index and gingivitis severity of children with intellectual disability - Alyzha Anandya; Linda Sari Sembiring; Henry Yonatan Mandalas (Padjadjaran Journal of Dental Researchers and Students, 2019)
Pendahuluan: Anak tunagrahita merupakan anak yang memiliki keterbatasan kemampuan kognitif dan mobilitas serta gangguan perilaku. Keadaan tersebut membatasi anak untuk melakukan pembersihan gigi yang optimal sehingga berdampak terhadap kondisi kesehatan gigi dan mulut seperti indeks plak yang buruk dan gingivitis. Tujuan penelitian ini adalah untuk mengetahui indeks plak dan tingkat keparahan gingivitis pada anak tunagrahita (intellectual disability). Metode: Penelitian ini dilakukan secara deskriptif komparatif. Populasi dalam penelitian ini ialah 45 anak tunagrahita di SLB Negeri Kota Bandung. Penarikan sampel dilakukan secara purposive sampling. Pengambilan data menggunakan metode O’Leary untuk indeks plak, dan metode Modified Gingival Index (MGI) untuk perhitungan skor gingiva. Hasil: Subjek penelitian dikelompokkan menjadi kelompok usia 8-12 tahun dan >28 tahun; serta berdasarkan jenis tunagrahita. Kelompok tunagrahita berat memiliki hasil index plak kurang baik sebesar 100%. Pada kelompok usia 13-17 tahun, didapatkan hasil karakteristik status gingiva paling besar (60%), sedangkan jika dilihat dari jenis tunagrahita, pada tunagrahita ringan memiliki gingivitis ringan (72,8%), tunagrahita sedang memiliki gingivitis sedang (62%), dan tunagrahita berat memiliki gingivitis ringan (50%) dan sedang (50%). Simpulan: Hampir setiap jenis tunagrahita memiliki indeks plak kurang baik dan gingivitis pada rongga mulutnya. Semakin rendah tingkat intelegensi anak maka semakin rendah kebersihan mulut, kecuali pada anak tunagrahita berat.Kata kunci: Indeks plak, tunagrahita, gingivitis, O’Leary, Modified Gingival Index ABSTRACTIntroduction: Children with intellectual disability are children who have limited cognitive abilities, mobility, and behavioural disorders. This situation limits the child to perform optimal dental cleaning so that it affects their dental and oral health conditions, such as poor plaque index and gingivitis. The purpose of this study was to determine the plaque index and the gingivitis severity of children with intellectual disability. Methods: This study was a descriptive comparative study. The population in this study were 45 children with intellectual disability in extraordinary schools in the city of Bandung. Sampling was taken by purposive sampling method. Data collection was using the O'Leary method for plaque indexes, and the Modified Gingival Index (MGI) method for calculating gingival scores. Results: The research subjects were grouped into 8-12 years old age groups and > 28 years old age group, and based on the type of intellectual disability. Severe intellectual disability groups have a poor plaque index of 100%. In the age group of 13-17 years old, the highest gingival status characteristics (60%) were found, whereas when analysed from the type of intellectual disability, moderate intellectual disability children had mild gingivitis (72.8%), moderate intellectual disability children had moderate gingivitis (62%), and severe intellectual disability children have both mild (50%) and moderate (50%) gingivitis. Conclusion: Almost every type of intellectual disability children have a poor plaque index and gingivitis in the oral cavity. The lower the children’s intelligence level, the lower the oral hygiene; except for children with severe intellectual disability.Keywords: Plaque index, intellectual disability, gingivitis, O’Leary method, Modified Gingival Index